C.2 The use of magnetic resonance guided focused ultrasound for refractory psychiatric illness. (November 2021) - Davidson, B; Meng, Y; Giacobbe, P; Hamani, C; Lipsman, N
Abstract : Background: Obsessive compulsive disorder (OCD) and major depressive disorder (MDD) are common, often refractory, neuropsychiatric conditions for which new treatment approaches are urgently needed. Magnetic resonance guided focused ultrasound (MRgFUS) is a novel surgical technique permitting incisionless ablative neurosurgery. Methods: We examined the safety profile, clinical response, and imaging correlates of MRgFUS anterior capsulotomy (MRgFUS-AC) in patients with refractory OCD (n=7) and MDD (n = 10). Results: There were no serious adverse clinical or radiographic events. 5/7 OCD patients and 3/10 MDD patients met pre-established clinical response criteria. Neurocognitive performance improved on several measures of executive function (p<0.05). By 6 months, there were significant reductions in cerebral glucose metabolism, and reductions in the bilateral tracts connecting the thalamus with the orbitofrontal cortices, anterior cingulate cortex (p<0.05). Preoperative functional connectivity between the right ventral striatum and hippocampus was predictive of eventual clinical response (p-FDR<0.05). Conclusions: MRgFUS-AC is safe and demonstrates important evidence of efficacy in treatment resistant psychiatric disease, particularly OCD. The procedure was associated with structural and metabolic changes in brain networks implicated in affective regulation, Resting-state fMRI offers the ability to predict response, and potentially select patients most likely to improve.